A comprehensive approach to health, safety, and environmental sustainability in drilling: Balancing operational efficiency with safety standards - Money, Barima; Siti Qurratu’ Aini, Mahat; Norasyikin, Ismail; Gbonhinbor, Jeffrey Randy; Modather, Rayan Hassan; Umunnawuike, Chika; Nwaichi, Peter Ikechukwu; Nyah, Francis; Abutu, David; Agi, Augustine Aja (Society of Petroleum Engineers, 2025)
The oil and gas drilling industry are inherently associated with significant health, safety, and environmental (HSE) risks due to the nature of operations and the complexities of the environment in which they take place. Achieving a balance between operational efficiency and stringent safety standards is crucial to ensure both the well-being of workers and the preservation of the environment. This paper presents a comprehensive approach to HSE management in drilling operations, highlighting the need for a holistic framework that integrates risk management, safety protocols, environmental stewardship, and regulatory compliance. It examines best practices and industry innovations aimed at minimizing hazards, reducing environmental impact, and enhancing the safety of workers. Through a review of existing literature, case studies, and industry standards, the paper explores how advanced technologies, such as automation and real-time monitoring, contribute to both operational efficiency and safety improvements. Furthermore, the paper discusses the role of safety culture, training, and continuous improvement in fostering a sustainable drilling environment. The findings underscore the importance of collaboration across all stakeholders to balance productivity with robust safety and environmental practices, ultimately ensuring sustainable drilling operations that are both economically and environmentally responsible.